Representaciones de dos cuidadores principales de familiares con enfermedad de alzheimer con relación a la sobrecarga que experimentan al cuidarlos (2020)
This is a research proposal related to the representations of caregivers of patients with Alzheimer's disease in relation to the overload they experience, the paradigmatic and epistemological bases that based this work, were given from systematic theory, hermeneutics and narratives, by Therefore, the methodology used for the investigative process was qualitative research with descriptive scope through a semi-structured interview. In accordance with this, the objective was to understand the representations of two caregivers patients with Alzheimer's disease in the city of Bogotá in relation to the overload they experience when providing care to their relatives, through the narrative elements Alzheimer's disease was addressed , quality of life, overload and coping as categories. Where it is concluded that there is a sustained decrease in social life and support networks in caregivers, this generates negative feelings in them, however, coping resources that allow them to fulfill their role adequately. It is important to note that the caregivers have sought support from health institutions to receive home care for their relatives, but it is on hold.